Adult Tobacco Cessation in Cambodia: I. Determinants of Quitting Tobacco Use. (September 2013) - Tonstad, Serena; Job, Jayakaran S.; Batech, Michael; Yel, Daravuth; Kheam, They; Singh, Pramil N.
This study determined factors associated with quitting tobacco in Cambodia, a country with a high prevalence of men who smoke and women who use smokeless tobacco. As part of a nationwide survey, face-to-face interviews were conducted with 5145 current and 447 former tobacco users who had quit for ≥2 years. Determinants of quitting in multivariate analyses were age >48 years, age at initiation >25 years, ≥7 years of education, income ≥1 US dollar per day, professional (odds ratio [OR] = 2.52; 95% confidence interval [CI] = 1.27-5.01) or labor (OR = 1.98, 95% CI = 1.10-3.56) occupations, and heart disease (OR = 1.94; 95% CI = 1.10, 3.42). Smokeless tobacco users were 10-fold less likely to quit (OR = 0.10; 95% = CI 0.05-0.20) than smokers. In conclusion, tobacco cessation among Cambodians was lower than in nations with decades of comprehensive tobacco control policies. Tobacco cessation programs and policies should include all forms of tobacco and target young to middle-aged users before onset of disease and premature death.